Efficacy of unblinded and blinded intermittently scanned continuous glucose monitoring for glycemic control in adults with type 1 diabetes - Guo, Lixin; Li, Yuxiu; Zhang, Mei; Xiao, Xinhua; Kuang, Hongyu; Yang, Tao; Jia, Xiaofan; Zhang, Xianbo (Frontiers in Endocrinology, 2023)
Objective Intermittently scanned continuous glucose monitoring (isCGM) is used for unblinded or blinded monitoring of interstitial glucose. We aimed to compare the efficacy of blinded and unblinded isCGM with the FreeStyle Libre system for glycemic control in adults with type 1 diabetes (T1D). Research design and methods This randomized clinical trial conducted between October 2018 and September 2019 across four endocrinology practices in China included 273 adults aged ≥18 years with T1D, who were randomly divided in a 2:1 ratio into the unblinded (n = 199) or blinded isCGM group (n = 78). In the blinded group, the clinician used FreeStyle Libre for monitoring, but self-monitoring was also performed by the patients. Results Two hundred sixteen (78%) participants completed the study (152 [75%] in the unblinded and 64 [82%] in the blinded group). At 12 weeks, a significant increase in TIR (3.9-10.0 mmol/L) was only observed in the unblinded group, along with a significant decrease in hyperglycemia (>13.9 mmol/L), hypoglycemia (<3.0 mmol/L), glycemic variability. Further, the mean HbA1c reduction from baseline to 12 weeks was 0.5 % in the unblinded isCGM group and 0.4% in the blinded isCGM group respectively (P < 0.001), but the significance did not remain after adjustment for between-group differences. Finally, 99.5% of the blinded isCGM values and 93.8% the of unblinded isCGM values were obtained at the final visit. Conclusions Unblinded isCGM was superior to blinded isCGM for glucose management, but nearly 100% of the attempted profiles were obtained successfully with the blinded isCGM system. Thus, combining real-time and retrospective data with isCGM might be the most impactful way to utilize flash glycemic monitoring devices.